A highly specific phosphatase from Saccharomyces cerevisiae implicated in tRNA splicing. - McCraith, S M (1990)
We identified and partially purified a phosphatase from crude extracts of Saccharomyces cerevisiae cells that can catalyze the last step of tRNA splicing in vitro. This phosphatase can remove the 2'-phosphate left over at the splice junction after endonuclease has removed the intron and ligase has joined together the two half-molecules. We suggest that this phosphatase is responsible for the completion of tRNA splicing in vivo, based primarily on its specificity for the 2'-phosphate of spliced tRNA and on the resistance of the splice junction 2'-phosphate to a nonspecific phosphatase. Removal of the splice junction 2'-phosphate from the residue adjacent to the anticodon is likely necessary for efficient expression of spliced tRNA. The phosphatase appears to be composed of at least two components which, together with endonuclease and ligase, can be used to reconstitute the entire tRNA-splicing reaction.